Pengaruh Profitabilitas, Struktur Modal dan Likuiditas terhadap Nilai Perusahaan dengan Green Competitive Advantage sebagai Pemoderasi - Gunawan, Henry; Tambun, Sihar; Thenesya, Fransisca (Media Akuntansi Perpajakan, 2025)
This study aims to examine the effect of profitability, capital structure, liquidity, and Green Competitive Advantage on firm value. Companies used by 50 companies in the mining sector listed on the Indonesia Stock Exchange during the period 2021-2023. The results of the study indicate that profitability has a significant effect on firm value and capital structure, liquidity does not have a significant effect on firm value. The results of the analysis show that the effect of green competitive advantage as a moderator is not significant on firm value. These results indicate that there are still other factors that may also play a role in influencing firm value that have not been included in this analysis. This study emphasizes that in order for a company to increase its value, the company must focus on efficient profit generation and effective management, while factors related to capital structure, liquidity, and sustainability, although important, may not directly affect investor perceptions of firm value.